The effect of work environment on employee productivity: a case study of manufacturing company / Muhammad Ammar Shafi ... [et al.] - Shafi, Muhammad Ammar; Le, Ng Siau; Zulkipli, Hafizah; Hasim, Muhammad Asyraf; Yusoff, Mohd Zarir (Faculty of Business and Management, 2023)
The work environment plays an important role in employee productivity. Due to the work environment is a set of relationships that exist between employees and the environment where they work. In addition, we can see that most of the common problems that affect the work environment and productivity of employees in manufacturing companies in Batu Pahat is that the workplace perspective of most companies is unhealthy and dangerous. Therefore, this study focuses on the effect of the work environment on employee productivity in a Batu Pahat manufacturing company. In this study, the researcher aims to identify the effect of the work environment on employee productivity in a Batu Pahat manufacturing company. Quantitative methods are used in this research. Questionnaires were distributed to 384 respondents in manufacturing companies in Batu Pahat. The response rate was 70.31% and data was collected and analyzed using the Statistical Package for Social Science (SPSS). The results of the descriptive analysis show that working conditions are the main effect of employee productivity in manufacturing companies in Batu Pahat. The physical work environment, working conditions and workplace layout have a significant relationship between employee productivity. This research will help research to know more about the effects of the work environment. This finding may be a reference for companies in manufacturing to know the work environment that can affect employee productivity.